Effect of Dried Eucheuma cottonii Stored in Seaweed Storage Device in Its Quality - Iwan Malhani Al Wazzan; Putri Wullandari; Ahmat Fauzi (Jurnal Perikanan Universitas Gadjah Mada, 2021)
A seaweed storage device in the form of a bunker has been developed by the Indonesian Research Institute for Fisheries Postharvest Mechanization. This study aimed to compare the quality of dried E. cottonii stored in the seaweed storage device and stored in the sacks placed in the room. Based on SNI 2690:2015, dried E. cottonii quality can be determined from its moisture content, impurities, Clean Anhydrous Weed (CAW), and Total Yeast and Mold Counts (TYMC). Moisture content was measured according to CAW, and contaminants were measured respectively according to SNI 01-2354.2-2-2006, SNI 8168:2015, and SNI 8169:2015. The results showed that moisture content of the seaweed stored in the bunker decreased by 27.17%, and that stored in the sacks decreased by 14.77%, signing a more significant weight loss during storage in the bunker. However, seaweed stored in the bunker has lower impurities (1.70±0.13 vs 1.84±0.13%), higher CAW (40.42±2.45 vs 38.75±2.45%), and TYMC (450±70 vs 2500±115.33 cfu/g).